Upcycling of abandoned banner via thermocatalytic process over a MnFeCoNiCu high-entropy alloy catalyst - Park, Chanyeong; Lee, Hansung; Lee, Nahyeon; Ahn, Byungmin; Lee, Jechan (Journal of Hazardous Materials, 2022)
High-entropy alloys (HEAs) are composed of five or more elements in a near-equimolar ratio. They have drawn increasing attention in catalytic applications owing to their unique properties to engineer surface composition and active sites. In this study, we aimed to apply a HEA of MnFeCoNiCu (atomic ratio of Mn/Fe/Co/Ni/Cu = 1) to a thermocatalytic process for upcycling abandoned banners, which are a common plastic waste material. To this end, the thermocatalytic conversion of the banner waste was compared with its non-catalytic thermal conversion at 500–900 °C. X-ray diffractometer and scanning electron microscopy-energy dispersive spectroscopy analyses confirmed that a single-phase face-centered-cubic (FCC) HEA was obtained, and each metal was distributed homogeneously in the HEA system with severe lattice distortion. The highly homogeneous nature and lattice distortion of the HEA resulted in catalytic effects on the thermal treatment of the banner waste. The HEA catalyst increased the yield of gas and liquid products. In the gas product, CO2 production was enhanced and CO production was suppressed, indicating that the HEA catalyst promotes decarboxylation and hinders decarbonylation during the thermal degradation of the banner waste. Utilizing the HEA catalyst resulted in more biphenyls and fluorenes in the liquid product, indicating that it promotes decarboxylation and dehydrogenation reactions during the thermal decomposition of the banner waste. Up to 300 % higher concentrations of phthalic acids (e.g., terephthalic acid and isophthalic acid), valuable bulk chemicals used to make polyethylene terephthalate (PET) bottles, textile fibers, and polyester films, were obtained using the HEA catalyst, and not the non-catalytic, banner waste treatment. The formation of byproducts such as wax and char was suppressed when the banner waste was treated in the presence of the HEA catalyst. Our preliminary results could offer insight into developing a new thermocatalytic process to recover value-added chemicals from plastic waste.
Keywords: Alloy catalyst; Atomic ratio; Gas product; High entropy alloys; Lattice distortions; Non-catalytic; Plastics waste; Thermo chemical process; Thermocatalytic process; Waste valorizations; High-entropy alloy; Plastic waste; Thermochemical process; Waste treatment; Waste valorization